Festival Communication: A Critical Analysis of Ukwuani People of Delta State - Okocha, Desmond Onyemechi; Faloseyi, Michael; Elele, Felix Chibuzo; Onobe, Melchizedec Jame (The Indonesian Journal of Communication Studies, 2024)
Beyond their abilities to facilitate social gatherings, festivals have been identified as a platform for communicating and transferring social values. This study investigated the role of festivals as a medium of communication among the Ukwuani ethnic nationality of Delta State. It further evaluated the challenges associated with using festivals as a communication tool. This quantitative study administered a questionnaire to purposively selected respondents from the three local government councils of Delta State, led by the Ukwuani ethnic group. The study relied on symbolic interactionism and ritual theories as theoretical frameworks. The study findings confirmed festivals as a means of communication among Ukwuani people and a platform for intergenerational transfer of values and social norms such as gifting to older adults. Notwithstanding, modernization, especially information and communication technology, impacts festival celebrations in many ways. Nonetheless, the most profound impact of modernization and ICT is reducing the youth's interest in festivals among the Ukwuani people. Recommendations to reverse this trend include deliberate efforts to explore the tourist potential of these festivals and more publicity to encourage corporate institutions' and marketers' involvement in festivals.